Difficulties of Translating Tenses from English to Arabic (Specialization students in linguistic and translation as a sample) - Abdul Majeed Mohammed Aaqil; Abdul Majeed Razick (Indonesian Journal of Arabic Studies, 2022)
The study aimed at detecting difficulties faced by translation students while translating the tense from English into Arabic. The researcher has used the Descriptive, Analytical and Contrastive methods. Moreover, the researcher used primary and secondary data. Primary data were obtained from questionnaire distributed to all male and female students who are studying specialization in linguistics and translation from Arabic department. The number of students are 42. Secondary data were collected from books, research articles and Websites information to construct its theoretical subject. In order to obtain accurate scientific results, the researcher used MS Excel 2019. Interviews were conducted randomly with three students in each year. The major findings are there are more differences then similarities in tense structure between two languages in terms of the number of tenses and its basis and the use of clues which indicates meaning. Therefore, students face difficulties when translating in identifying tense, choosing the right word, and usage of appropriate clues for tense. They also face difficulties in translating tense, especially in perfect and perfect continues tenses. In order to reduce the difficulties, the researcher suggest that students should focus on learning tense accurately with practical. This research would help identify difficulties in translating tense and provide appropriate solutions regarding the issue